Barnacle cover modifies foraging behaviour of the intertidal limpet Patella vulgata. (10th September 2019) - Santini, Giacomo; Thompson, Richard C.; Jenkins, Stuart R.; Chelazzi, Guido; Hartnoll, Richard G.; Kay, Suzanne M.; Hawkins, Stephen J.
Abstract: Limpets and barnacles are important components of intertidal assemblages worldwide. This study examines the effects of barnacles on the foraging behaviour of the limpet Patella vulgata, which is the main algal grazer in the North-west Atlantic. The behaviour of limpets on a vertical seawall on the Isle of Man (UK) was investigated using autonomous radio-telemetry, comparing their activity patterns on plots characterized by dense barnacle cover and plots from which the barnacles had been removed. Limpet behaviour was investigated at mid-shore level, but two different elevations were considered. This experiment revealed a significant effect of barnacle cover on the activity of P. vulgata . Limpets on smooth surfaces spent a greater proportion of total time active than did limpets on barnacles. Movement activity was also greater in areas that were lower down in the tidal range. In general, limpets were either predominantly active during diurnal high or nocturnal low tides and always avoided nocturnal high tides. Individuals on barnacles at the higher elevation concentrated their activity during nocturnal low water. All the other groups of limpets (smooth surfaces on the upper level and all individuals on the lower shore) had more excursions centred around daylight hours with an equal distribution of activity between periods of low and high water. Inter-individual variability was, however, pronounced.